Immune imprinting and vaccine interval determine antibody responses to monovalent XBB.1.5 COVID-19 vaccination - Xammy Huu Wrynla; Timothy A. Bates; Mila Trank-Greene; Mastura Wahedi; Audrey Hinchliff; Marcel E. Curlin; Fikadu G. Tafesse (Communications Medicine)
Abstract Background As COVID-19 becomes endemic and vaccines are annually adapted, exposure intervals and immune imprinting become critical considerations for vaccination strategy. Imprinting by the ancestral spike protein affected bivalent Wuhan-Hu-1/BA.4-5 vaccine responses. We assess the persistence of imprinting in antibody responses to the more recent XBB.1.5 monovalent formulation. Methods We quantified live virus-neutralizing antibodies by focus reduction neutralization test and ancestral spike receptor-binding isotype titers by immunosorbent assay in individuals before and after XBB.1.5 vaccination. We compared responses between those who previously received three to four doses of Wuhan-Hu-1 vaccine and one dose of bivalent Wuhan-Hu-1/BA.4-5 (bivalent recipients) and those who received three to four doses of Wuhan-Hu-1 (bivalent non-recipients). Results We report that before XBB.1.5 vaccination, bivalent non-recipients have decreased breadth and potency of neutralization. At post-vaccination, non-recipients exhibit greater boosting of neutralizing antibodies against XBB.1.5 (18.4X versus 6.2X), EG.5.1 (30.9X versus 7.0X), and JN.1 (9.2X versus 3.7X) variants with comparable breadth and trends toward greater potency. Greater boosting in non-recipients is similarly observed for spike-binding IgA and total IgG/A/M but not IgG nor IgM. Bivalent non-recipients had longer intervals between vaccination, which may enhance antibody responses; however, bivalent receipt and interval are tightly linked, preventing isolation of individual contributions to boosting. Nonetheless, back-boosting of ancestral SARS-CoV-2 titers in both participant groups provides interval-independent evidence that imprinting persists. Conclusions Our findings indicate that immune imprinting continues to affect humoral immunity elicited by the XBB.1.5 vaccine. Both imprinting and exposure intervals are important phenomena underlying immunogenicity of future variant-adapted COVID-19 vaccines.